2018
DOI: 10.1186/s12884-018-1706-4
|View full text |Cite
|
Sign up to set email alerts
|

De-medicalization of birth by reducing the use of oxytocin for augmentation among first-time mothers – a prospective intervention study

Abstract: BackgroundThe use of synthetic oxytocin for augmentation of labor is rapidly increasing worldwide. Hyper-stimulation is the most significant side effect, which may cause fetal distress and operative delivery. We performed an intervention consisting of an educational program and modified guidelines to achieve a more appropriate use of oxytocin.MethodsThis prospective intervention study included 431 first-time mothers at term with spontaneous onset of labor before (October 2012 to May 2013), and 664 after the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
(50 reference statements)
3
20
0
3
Order By: Relevance
“…It has been shown than multiparous women in this study were less exposed to the risk of experiencing non-spontaneous vaginal births compared with primiparous women [30], but when multiparous women in the study were administered oxytocin, they were significantly at greater risk of suffering non-spontaneous vaginal birth. (OR 3.05; CI 95%: 1.28–7.30, p -0.01) vs (OR 1.23; CI 95%: 0.68–2.24, p -0.49).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…It has been shown than multiparous women in this study were less exposed to the risk of experiencing non-spontaneous vaginal births compared with primiparous women [30], but when multiparous women in the study were administered oxytocin, they were significantly at greater risk of suffering non-spontaneous vaginal birth. (OR 3.05; CI 95%: 1.28–7.30, p -0.01) vs (OR 1.23; CI 95%: 0.68–2.24, p -0.49).…”
Section: Resultsmentioning
confidence: 76%
“…For, intrapartum care for healthy women and babies, the NICE guidelines recommend not to routinely offer interventions (such as active management of labour, amniotomy and oxytocin) during the first stage of labour [10]. Therefore, the guidelines for labour dystocia and augmentation, based on the latest evidence should be followed, allowing labour to progress uninterrupted, and respecting its normal progress without rushing it, especially in view of Gaudernack et al’s study which shows the association between the use of oxytocin and instrumental births [30]. The NICE guidelines recommend to actively intervene in very specific cases where labour delay is confirmed (i.e., if delay in first stage of labour with ruptured membranes if cervical dilatation less than 2 cm in 4 h, NICE guidelines recommends starting oxytocin) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, the Birthplace study had a selected population of low-risk women. Judicious use of oxytocin has been associated with a reduction in emergency CS in several studies 32 while other studies have found no increase in CS 34 . There were no cases of ruptured uterus among women receiving oxytocin, suggesting careful use of oxytocin at the study site, in particular when over half of the multiparous women had a previous CS.…”
Section: Discussionmentioning
confidence: 99%
“…Aber erst die synthetische Herstellung durch Vigneaud und Kollegen in den 50er Jahren des vorherigen Jahrhunderts, führte zu seiner festen Etablierung in der Geburtshilfe [27]. Verschiedene Analysen unter Erstgebärenden in den USA ergaben, dass der Oxytocingebrauch zur Einleitung oder Wehenunterstützung zwischen 37 und 75 % lag [16]. In Deutschland lag die Rate 2014 bei 27 % aller Geburten.…”
Section: Synthetisches Oxytocinunclassified